Impact of Financial Leverage on Profitability of Reliance Industries LTD - Priyanka Meghanathi; Alok Chakrawal (Newinera Publisher, 2021)
Oil and gas sector is among the eight core industries in India and plays a major role in influencing decision making for all the other important sections of the economy. The main purpose of the study is to examine the impact of financial leverage on the profitability of reliance industries ltd. The study verifies two hypotheses first is There is no significant relationship between financial leverage with Profitability and Second one There is no significant impact of financial leverage on profitability of Reliance Industries Ltd during the study period. Financial leverage is taken as independent variable and Net Profit Ratio (NPR), Earning per share (EPS), Return on Equity (ROE) and Return on Asset (ROA) are taken as dependent variable. The data collected over period of 2016-17 to 2020-21 regarding financial leverage and profitability from annual consolidated financial statement of Reliance Industries Ltd. Correlation is used to know the relationship between financial leverage with Profitability. Linear regression is used to examine the impact of leverage on profitability. The results showed that there is no significant relationship between financial leverage with NPR and significant positive relationship between financial leverage with EPS, ROE and ROA. Regression result shows that there is no significant impact of leverage on profitability of reliance industries ltd during the study period.